Academic and sport achievements of the physical culture and sports university students - Ihor Zanevskyy; Lyudmyla Zanevska (IP Iermakov S.S., 2021)
Background and Study Aim. It is widely used a paradigm about the interdependence between the academic and sport achievements of students. The aim of this research was to create a model for studying relationships between academic and sport achievements of the sports and physical culture university students. Material and Methods. Totally 259 (168 male and 91 female) bachelor students of 18-23 years old studied Physical Culture and Sports were involved into the investigation. All the students were good healthy, and they participated in the sport training and competitions, according the common program. Interdependence between the semester control scores and scores of the sport achievements were studied in the frames of correlation models of parameter and non-parameter statistics. Distribution of scores was studied using Kolmogorov - Smirnov method. One-way ANOVA for repeated measures was used to determine differences between students' scores and educational disciplines' scores. Results. Almost non-significant weak interdependence between results of the semester control and sport achievements was noticed (р>0.05, 0.174≤rs≤0.284). There were no statistically significant and tight correlation between semester control scores of educational disciplines and corresponding sport achievements scores (|rs|≤0.376). Contrary, in 73% of educational disciplines pairs the semester control scores showed significant and tight correlation (p<0.001, 0.385≤r≤0.895). Conclusions. A well-known paradigm about significant relationship between academic and sport achievements of students was not confirmed with the results of this research and should be studied more profoundly.